Job Satisfaction and Employee Turnover: Analysis Recruitment, Career Development, Organizational Culture - Candra Susanto, Primadi; Ni Nyoman Sawitri; Dewi Susita (Dinasti International Journal of Digital Business Management, 2023)
The purpose of the study is to see the relationship between variables and provide answers from the perspective of researchers’ methods use qualitative techniques in ways related to literature, and review literature which is a way or method of scientific writing in the form of library research. The results of the research on the variables in this study according to the review literature that between variables there is a direct and positive influence even though there are variables as independent variables, intervening variables, and dependent variables. Dozens of review literature displayed in this study were analyzed using variables in this study.